2008
DOI: 10.1007/s00268-008-9600-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Sonographic Features in Preoperative Evaluation of Malignant Thyroid Nodules in a Multinodular Goiter

Abstract: Although we did not identify a single feature indicative of malignancy in the sonographic examination of nodules, microcalcification and blurred margin were the strongest correlates for malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
9
37
0
3
Order By: Relevance
“…4 These features have been identified as major predictors of malignancy in thyroid nodules in similar studies also. 5 According to the 2015 American Thyroid Association Guideline Task Force, solid component hypoechoic thyroid nodules with one or more of the following features have over 70-90% risk of malignancy: irregular margins, micro-calcifications, taller than wide shape, and rim calcifications. 6 In the present study, for detection of malignancy ultrasound has a sensitivity of 87.2%, specificity of 79.2%, positive predictive value of 89.1 %, negative predictive value of 76% and an overall accuracy of 84.5%, which is in concordance with literature.…”
Section: Discussionmentioning
confidence: 99%
“…4 These features have been identified as major predictors of malignancy in thyroid nodules in similar studies also. 5 According to the 2015 American Thyroid Association Guideline Task Force, solid component hypoechoic thyroid nodules with one or more of the following features have over 70-90% risk of malignancy: irregular margins, micro-calcifications, taller than wide shape, and rim calcifications. 6 In the present study, for detection of malignancy ultrasound has a sensitivity of 87.2%, specificity of 79.2%, positive predictive value of 89.1 %, negative predictive value of 76% and an overall accuracy of 84.5%, which is in concordance with literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported sensitivity and specificity values in our study correlate with those reported in the literature, with microcalcifications and irregu lar margins representing the most sensitive and specific tests available for stratifying malignant risk. [23][24][25][26] The TI-RADS scoring criteria were developed to help address the challenge of stratifying the risk of malignancy in thyroid nodules, which are prevalent in up to 60% of the general population. 3,12,13 The most recent studies examining TI-RADS, both prospectively and retrospectively, allow for a clear distinction between malignant and benign nodules in the vast majority of cases when all scoring criteria are applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, microcalcification and marginal iregularity which are associated with malignancy were similar in exophytic and nonexophytic groups. Solid consistency is more common in malignant thyroid nodules and the vast majority (82% -91%) of thyroid cancers are solid (10)(11)(12). In a study including 360 consecutively surgically removed thyroid cancers, 88% were reported to be solid or minimally cystic (13).…”
Section: Discussionmentioning
confidence: 99%